A simple synthesis route for preparation and optical properties of PMMA-g-ZnO nanocomposites through surface-initiated radical polymerization - Bach, Long Giang; Nguyen, Duy Chinh; Nguyen, Phu Thuong Nhan; Tran, T. H.; Islam, Md. Rafiqul; Lim, Kwon Taek; Vo, Dai-Viet N.; Nguyen, Trinh Duy (IOP Publishing, 2019)
An effortless chemisorption access for the planning of nanocomposites containing a semiconductor ZnO nanoparticles and poly(methyl methacrylate) (PMMA) is demonstrated. First, thiol-functionalized ZnO (ZnO-SH) were prepared by a silanization reaction between ZnO nanoparticles and (3-mercaptopropyl) trimethoxysilane. Then, a reserved radical polymerization of methyl methacrylate in the attendance of Zinc oxide-thiol (ZnO-SH) and butyrolactam produced PMMA-g-ZnO nanocomposites. DSC were used to examine the weight decline of glass transition temperature of nanocomposites. The ocular characteristics of the nanocomposites were studied by Ultraviolet-visible (UV–vis) absorption spectroscopy and photoluminescence spectroscopy (PL). The results accentuate the role of the grafted PMMA polymer segments in augmenting the strength of dispersal and near-band edge (NBE) emission of ZnO nanoparticles.